2018
DOI: 10.20319/pijss.2018.33.11441172
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self-Efficacy on Learners’ Perceptions of Cognitive Presence in Online Collaborative Learning Activities

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…It has been discovered in their study that this assertion would significantly impact the motivation of the learners to exert effort. Subsequent research by Wang and Shan [49] corroborated these findings by arguing that students' self-efficacy levels correlate with their level of effort and perseverance in school, and hence, their level of knowledge. Ong et al [21] demonstrated that it is an element influencing future intentions to get further information by pursuing chemistry-related courses.…”
Section: H8 Learning Through Perception and Understanding Alongside C...mentioning
confidence: 89%
See 1 more Smart Citation
“…It has been discovered in their study that this assertion would significantly impact the motivation of the learners to exert effort. Subsequent research by Wang and Shan [49] corroborated these findings by arguing that students' self-efficacy levels correlate with their level of effort and perseverance in school, and hence, their level of knowledge. Ong et al [21] demonstrated that it is an element influencing future intentions to get further information by pursuing chemistry-related courses.…”
Section: H8 Learning Through Perception and Understanding Alongside C...mentioning
confidence: 89%
“…According to Ong et al [13], children who seem to be confident in their capacity to learn indicate a drive to study, which encourages them to think critically. However, Wang and Shan [49] argued that learners with varying levels of SE demonstrate consistency with efforts and persistence, which raises the likelihood that it will have an influence on their level of cognition. In addition, the indicators of E showed that learners utilize different sources, explore, and resolve content-related questions and find a better perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In their empirical study, Davidson et al (2012) [3] found that raising students' self-confidence had a favourable correlation with their academic performance. Among other social and developmental factors, Wang and Shan (2017) [14] suggest that early socialisation patterns that favour men in computer-related activities may contribute to the gender gap in academic self-efficacy and achievement. Various elements, such as socialisation, social environment, and individual qualities, may impact children's academic self-efficacy and achievement, according to the statement.…”
Section: Discussionmentioning
confidence: 99%
“…The 20-item measure has 5 answer choices, including "strongly agree," "agree," "neutral," and "disagree," on a Likert-type scale. The scale assesses four aspects of self-efficacy: certainty in one's abilities (1, 2, 3, 4), belief in one's ability to achieve their goals (6,7,8,9), outlook on life (11,12,13,14,15), and anticipation of their actions' consequences (16,17,18,19,20). It was discovered that the self-efficacy measure has a test-retest reliability of 0.82 and a construct validity of 0.92, which indicates that it is reliable and valid.…”
Section: Toolmentioning
confidence: 99%
“…This learning and teaching change in higher education is experienced by the first-year students just as they join HEIs. Collaborative work is one method that can be used for a student-centred learning approach (Wang and Shan, 2017).…”
Section: Unfamiliar To Collaborative Workingmentioning
confidence: 99%